Numerical studies on sub-10 nanometer resolution imaging in electrostatic force microscopy. Issue 182 (24th July 2017) - Xu, Honglei; Zhao, Liangbing; Ding, Xidong; Lin, Guocong; Chen, Dihu
ABSTRACT: The lateral resolutions of electrostatic force microscopy (EFM) are systematically simulated using the boundary element method, considering a bimetallic sample with surface potential inhomogeneities as a special case. Two widely used modulation modes in EFM, namely, amplitude modulation (AM) for ambient EFM and frequency modulation (FM) for vacuum EFM, are compared for tip-sample separation ranging from sub-nanometer to 100 nm, and for various geometries and diameter of the probe. Different from the conventional viewpoint, the simulation results obtained in this study suggest the feasibility of realizing sub-10 nm lateral resolution in ambient AM-EFM using a small tip-sample separation in the order of 5 nm. This is almost the same as that of FM-EFM under vacuum. Furthermore, the simulation results are consistent with the reported experimental results. On the basis of the results, the optimal experimental parameters necessary for realizing sub-10 nm resolution imaging in ambient EFM are suggested.